Hellenism and the local communities of the Eastern Mediterranean : 400 BCE-250 CE - Chrubasik, Boris; Chrubasik, Boris; King, Daniel; King, Daniel (Oxford University Press, 2017)
The conquest of Alexander the Great was a catalyst for change throughout the Eastern Mediterranean, opening up new spaces for interaction between Greek and non-Greek cultures. In exploring these, this volume reassesses the concepts of 'Hellenism' and 'Hellenization' and their usefulness for understanding cultural exchange in this region and era